Aligning the Language Criteria of a Group Oral Test to the CEFR: The Case of a Formal Meeting Assessment in an English for Occupational Purposes Classroom - Priscilla Shak; John Read (UPM Press, 2021)
The Malaysian Education Blueprint (MEB) 2015-2025 has set in motion efforts from all stages of education to align programs, courses, and syllabuses to the Common European Framework of Reference (CEFR) benchmark. This exercise has brought on major revamps in all aspects of English language education in the nation. This study will present such an undertaking in a public university in Malaysia and detail how the language criteria for an oral group test of an English for Occupational Purposes course have been aligned to the stipulated CEFR level. The actual assessment task involved groups of four or five students conducting a meeting of their established company. Data for the study came from an analysis of the audio recordings of nine group meetings, along with post-assessment interviews and focus group discussions involving three EOP instructors. Based on the data analysis, this study recommends a revised set of language criteria for the assessment. Furthermore, it demonstrates how an alignment of the scoring criteria with the descriptors of the targeted CEFR scale can be achieved through a systematic comparison of the language functions (LFs) produced in the meeting task to the targeted CEFR descriptor scales. The revised language component for the meeting assessment could help ease instructors’ assessment of students interactional skills and allow them to gauge better their students’ attainment of the skills required in a formal meeting context.